Critical Testing Processes : Plan, Prepare, Perform, Perfect - Black, Rex (Addison-Wesley Professional, 2003)
The advent of agile methodologies and test-driven development has brought software testing to the forefront of application development. Yet in today's harried rush-to-market development environment, organizations must find a delicate balance between product release and product quality. In Critical Testing Processes, the author distills knowledge gained from 20 years of testing experience into twelve critical processes. These include highly visible processes by which peers and management judge competence, and mission-critical processes in which performance affects the company's profits and reputation. After each process is introduced, the author demonstrates its use through an engaging case study. Instead of cumbersome regulations, this book provides checklists-lightweight, flexible tools for implementing process-oriented testing, gathering metrics, and making incremental process changes. By demonstrating critical processes in various organizational, operational, and technological contexts, this book shows readers how to: Handle recurrent tests efficiently and consistently Develop a cohesive, cooperative team that sidesteps redundancies Build a reputation for reliability through the effective communication of test results Define the focus of tests for maximum customer satisfaction and organizational success Because testing is a collaborative process with the participation of staff throughout the organization, the author discusses interpersonal and cultural issues in depth. This book also devotes ample coverage to the often-overlooked areas of planning and perfecting tests. Whatever your role in testing-from test engineering to managing hundreds of test engineers- Critical Testing Processes will offer valuable insights into what you do, why it's important, and how you can perform better. 0201748681B04222003.